Perbedaan Fungsi Kognitif dan Keseimbangan Tubuh pada Lanjut Usia di Urban dan Rural: Differences in Cognitive Function and Postural Balance in Elderly Living in Urban and Rural Elderly - Komalasari, Dwi Rosella; Sari, Mely Erlika; Masitha, Sita (Jurnal Sains dan Kesehatan, 2024)
The incidence of falls increases in the elderly, with the risk of injury and death. Cognitive function is important in maintaining body balance. Differences in rural and urban areas affect cognitive function and balance in the elderly. This observational study involved 188 elderly from both areas, with a t-test used to determine differences in cognitive function and body balance between elderly in rural and urban areas, while the relationship between cognitive function and body balance was analyzed using the Pearson Correlation test, and Simple Linear Regression. The results showed that there were significant differences between cognitive function, and static and dynamic balance between the elderly in rural and urban areas (p<0.05). Both areas have many elderly with a high fall risk category. However, the elderly in rural areas are higher than in urban areas. Decreased cognitive function will reduce static balance by 95.1% in rural elderly. This identification is important for rehabilitation management, reducing the risk of falls in the elderly. Keywords:          Cognitive function, balance, elderly, rural, urban   Abstrak Angka kejadian jatuh meningkat pada lanjut usia, dengan risiko cedera hingga kematian. Fungsi kognitif penting dalam menjaga keseimbangan tubuh. Perbedaan lingkungan rural dan urban memengaruhi fungsi kognitif dan keseimbangan lansia. Studi observasional melibatkan 188 lansia dari kedua lingkungan, dengan uji t-test digunakan untuk mengetahui perbedaan fungsi kognitif dan keseimbangan tubuh antara lansia di rural dan di urban, sedangkan hubungan antara fungsi kognitif dan keseimbangan tubuh dianalisis menggunakan uji Pearson Correlation, dan Regresi Linear Sederhana. Hasil menunjukkan terdapat perbedaan signifikan anatara fungsi kognitif, keseimbangan statik dan dinamik antara lansia di rural dan urban (p<0.05). Kedua area mempuyai jumlah lansia yang tinggi dengan kategori resiko jatuh tinggi. Tetapi lansia di rural lebih tinggi daripada di urban. Penurunan fungsi kognitif akan menurunkan keseimbangan statik sebesar 95.1% pada lansia di rural. Identifikasi ini penting untuk manajemen rehabilitasi, mengurangi risiko jatuh pada lansia. Kata Kunci:         Fungsi kognitif, keseimbangan, lanjut usia, rural, urban